EDUKASI HIGIENE PERSONAL PENJAMAH MAKANAN DALAM RANGKA PEMBERDAYAAN KETERAMPILAN KELOMPOK USAHA WANITA TANI DI DESA MEKARBUANA KAB. KARAWANG - Putri Ronitawati,; Intan Dwi Asmarani,; Vitria Melani,; Elistia,; Siti Badriyah,; Septia Rosdyaningrum, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
A women's farmer business group in Mekarbuana village, Kab. Karawang, is participating in this community service activity. In order to boost the abilities of women farmer business groups in Mekarbuana village, this project intends to provide instruction about personal cleanliness for food handlers. Women farming business groups in Mekarbuana village have limited knowledge of hygiene and food safety. As a result, women farming business groups in Mekarbuana village need to be educated on the importance of personal hygiene and food safety in food processing so that they can broaden their knowledge of food hygiene and safety and ensure that consumers feel safe when eating the resulting food. The lecture method is being used to deliver the education. It was determined from the results of this activity that knowledge increased after being educated, so it was suggested that the activity be carried out by health workers and continued with constant monitoring or observation.